Characterization of biofouling with 3D-printed spacers using 3D optical coherence tomography - Chung, Ling Hao (2019)
Biofouling in membrane filtration is a common occurrence which impedes the efficiency of the separation process. By looking into the biofouling mechanisms via the observation of a filtration process, potential problems can be addressed and resolved. This study uses optical coherence tomography (OCT) to investigate the effects of using different 3D-printed spacers on the biofouling process. A compilation of OCT scans of a representative unit cell of each spacer was taken as a function of time to generate 3D-images showing the morphology of a foulant layer. Through the usage of various quantitative analysing methods (such as EIS, DOTM and etc), the development of a foulant layer was obtained. Thus, showing the various biofouling mechanisms involved in a biofouling process.